2013
DOI: 10.1177/2050312113516111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pharmacist counseling in improving knowledge, attitude, and practice in chronic kidney disease patients

Abstract: Background:Chronic kidney disease is a public health problem with an increasing incidence and prevalence, poor outcomes, and high cost. Patient involvement forms the keystone in the management of chronic kidney disease. This study evaluated effects of pharmacist-provided counseling in dialysis patients in terms of their knowledge, attitude, and practice outcomes.Methods:A total of 64 patients with chronic kidney disease were enrolled into the prospective, pre–post study based on the inclusion and exclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
2
21
0
1
Order By: Relevance
“…Pharmacist counseling has been shown to improve patient and parental knowledge on various chronic conditions . Education plays a vital role in AD management given its chronicity and treatment complexity .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Pharmacist counseling has been shown to improve patient and parental knowledge on various chronic conditions . Education plays a vital role in AD management given its chronicity and treatment complexity .…”
Section: Discussionsupporting
confidence: 78%
“…Pharmacist counseling has been shown to improve patient and parental knowledge on various chronic conditions. 10,11 Education plays a vital role in AD management given its chronicity and treatment complexity. 14 Shin et al showed that knowledge scores of caregivers who received a structured educational program were significantly higher than those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Education of patients about the management of DM was shown to lower the HbA1c level by 0.3-0.76% [4,5]. The purpose of this study was to assess the impact of pharmacist-led provision of drug-related information and patient education on treatment adherence by patients to achieve successful therapy.…”
Section: Introductionmentioning
confidence: 99%